Pengaruh Pemberdayaan Dan Motivasi Terhadap Kinerja Karyawan PT. Honda Balindo Cabang Luwuk: The Effect of Empowerment and Motivation on Employe Performance of PT. Honda Balindo Luwuk Branch - Kamaru, Sri Mulyaningsih; Milang, Ichsan; Yuliantari, Ni Wayan (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2024)
PT. Honda Balindo is a company engaged in the sale of cars, especially Honda. The formulation of the problem is how the influenceof empowerment and motivation on employee performance at PT. Honda Balindo Luwuk Branch. A type of qualitative data that isquantitative. The population is 10 people. The method used is the multiple linear regression analysis method and correlationcoefficient, determination, validity and feasibility test and T and F Statistical Test. Based on the results of the multiple linearregression analysis between empowerment and motivation on employee performance, the regression results are obtained with apositive and significant value where constant or fixed is -7.357, if there is an increase of 1 unit between the empowerment andmotivation variables, employee performance will increase 0.478 and 0.712. This is shown with a tcal value of 2.577 for X1 and a tcalof 3.481 for X2 while the ttable is 2.364. This means that if the tcount > ttable, Ho is rejected Ha is accepted. Based on the results ofthe correlation coefficient, the value of R = 0.989 was obtained, which means that the level of relationship is very strong. This meansthat there is a simultaneous or real relationship between empowerment, motivation and employee performance